Encontros e desencontros entre autonomia e sexualidade de adolescentes do Instituto Querô em Santos/SP - Esteves, Gabriela (2017)
This research sought to understand the notion of autonomy in the experience of sexuality among adolescents enrolled in Instituto Querô, an organization that works with young people in the municipality of Santos / SP. It sought to examine what adolescents think about Sexual and Reproductive Rights and about access to public policies in the sphere of sexuality. We sought to understand the process of constructing the autonomy of these adolescents as subjects of their own sexuality. It is a qualitative research that used the semi-structured interview modality for data collection and content analysis, with a documentary approach and the use of theoretical categories to understand the themes sexuality, adolescence and autonomy. The study revealed that adolescents differently think about sexual and reproductive rights, about public policies for adolescents. The autonomy they are experiencing is in the process of being built and is still based on the decisions of the parents. Adolescents point to the lack of transversality of the theme sexuality in school and from a perspective that reduces it to heterosexuality. Access to pornography stood out among adolescents, but was negatively assessed as an incentive to idealize bodies and violence against women. The study pointed out that the Querô Institute promoted new knowledge to adolescents, making them more critical and reflexive, about their own rights as subjects.